Combined Theoretical and Experimental Studies of Nickel-Catalyzed Cross-Coupling of Methoxyarenes with Arylboronic Esters via C–O Bond Cleavage - Schwarzer, Martin C; Konno, Ryosuke; Hojo, Takayuki; Ohtsuki, Akimichi; Nakamura, Keisuke; Yasutome, Ayaka; Takahashi, Hiroaki; Shimasaki, Toshiaki; Tobisu, Mamoru; Chatani, Naoto; Mori, Seiji (Journal of the American Chemical Society, 2017)
Nickel(0)-catalyzed cross-coupling of methoxyarenes through C–O bond activation has been the subject of considerable research because of their favorable features compared with those of the cross-coupling of aryl halides, such as atom economy and efficiency. In 2008, we have reported nickel/PCy3-catalyzed cross-coupling of methoxyarenes with arylboronic esters in which the addition of a stoichiometric base such as CsF is essential for the reaction to proceed. Recently, we have also found that the scope of the substrate in the Suzuki–Miyaura-type cross-coupling of methoxyarenes can be greatly expanded by using 1,3-dicyclohexylimidazol-2-ylidene (ICy) as the ligand. Interestingly, a stoichiometric amount of external base is not required for the nickel/ICy-catalyzed cross-coupling. For the mechanism and origin of the effect of the external base to be elucidated, density functional theory calculations are conducted. In the nickel/PCy3-catalyzed reactions, the activation energy for the oxidative addition of the C(aryl)–OMe bond is too high to occur under the catalytic conditions. However, the oxidative addition process becomes energetically feasible when CsF and an arylboronic ester interact with a Ni(PCy3)2/methoxyarene fragment to form a quaternary complex. In the nickel/ICy-catalyzed reactions, the oxidative addition of the C(aryl)–OMe bond can proceed more easily without the aid of CsF because the nickel-ligand bonds are stronger and therefore stabilize the transition state. The subsequent transmetalation from an Ar–Ni–OMe intermediate is determined to proceed through a pathway with lower energies than those required for β-hydrogen elimination. The overall driving force of the reaction is the reductive elimination to form the carbon–carbon bond.